Overview Of Behaviors To Prevent Transmission Of Pulmonary Tuberculosis In Families In The Sokaraja 1 Community Health Center Working Area - Defitri Siregar; Ikit Netra Wirakhmi; Siti Haniyah (CV. AFDIFAL MAJU BERKAH, 2026)
Pulmonary tuberculosis remains a major health problem in Indonesia, particularly in high-prevalence areas such as Sokaraja 1 Community Health Center, Banyumas, where families play a crucial role in preventing transmission. This study aims to describe the behavior of preventing pulmonary tuberculosis transmission in families of sufferers. Using a quantitative descriptive cross-sectional design with a univariate approach, a population of 89 families was sampled via total sampling. A 10-item Likert questionnaire instrument (validity r=0.582-0.734; reliability α=0.817) was analyzed univariately using SPSS (frequency, mean, table). The results showed that the majority of respondents were female (73%), aged 36-45 years (34.8%), had junior high school education (38%), and were housewives (49.4%), with negative (76.4%) versus positive (23.6%) prevention behaviors. The conclusion suggests that suboptimal behavior indicates the need for intensive education to improve household compliance to reduce TB transmission.